Монгол улсын аймаг, хотуудын хүн амын цацрагийн гадаад шаралтын тун - Д, Шагжжамба; Ж, Ганзориг; Б, Далхсүрэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper results of estimation of the radiation exposure, obtained by populations of the cities and province’s canters according to the studies on the radiation burden among the population and radioactivity of environment by the Nuclear Research laboratory of the National University of Mongolia since 1985. It was estimated separately all three sources of the population exposure, cosmic ray, outdoor and indoor radiation exposure, caused by soil natural and building material radioactivity and the maximum volume of annual average of effective dose equivalent external dose rate of population was determined as 1180 mikrosivert.